Dietary Palygorskite-Based Antibacterial Agent Supplementation as an Alternative to Antibiotics Improves Growth Performance, Blood Parameters, and Rumen Microbiota in Sheep - Shujie Li; Yue Liu; Hanfang Zeng; Chanjian Wang; Zhaoyu Han (MDPI AG, 2023)
This research aimed to investigate the effects of a palygorskite-based antibacterial agent (PAA) as an alternative to antibiotics on growth performance, blood parameters, and rumen microbiota in sheep. A total of 120 sheep were randomly divided into five groups of six replicates with four sheep each. Sheep were fed a basal diet, an antibiotic diet supplemented with 500 g/t chlortetracycline (CTC), and a basal diet supplemented with 500, 1000, and 2000 g/t PAA for 80 d, respectively. Supplementation with 2000 g/t PAA and 500 g/t CTC increased the average daily gain (ADG) of sheep compared with the control group (p < 0.05). Diets supplemented with 2000 g/t PAA and 500 g/t CTC reduced (p < 0.05) the feed:gain ratio (F/G ratio) in the overall periods. Dietary supplementation with 1000 g/t PAA significantly increased albumin and total protein (p < 0.05). A significant positive correlation was found between growth hormone concentration and PAA supplementation (p < 0.05). In addition, compared to the control group, the CTC group had higher growth hormone concentration and lower lipopolysaccharide concentration (p < 0.05). No difference was observed between the five groups in terms of rumen fermentation characteristics (p > 0.05). At the phylum level, the relative abundance of Proteobacteria was lower in the PAA 2000 and CTC 500 groups than in the control and PAA 500 groups (p < 0.05). At the genus level, a significant decrease (p < 0.05) in the relative abundance of RuminococcaceaeUCG-010 was observed in the PAA 1000, PAA 2000, and CTC 500 groups compared with that in the control group. In addition, the relative abundance of Prevotella1 (p < 0.05) was higher in the PAA 2000 group than in the control group. These findings indicate that dietary supplementation with PAA has ameliorative effects on growth performance, blood parameters, and rumen microbiota, with an optimal dosage of 2000 g/t for sheep.